Analisis Berpikir Kritis Mahasiswa Mata Kuliah Kimia Dasar Materi Ikatan Kimia - Aisyiah Restutiningsih Putri Utami; Mustapa Mustapa; Miftahul Jannah; Ermita Ermita; Ayu Fahimah Diniyah Wathi (Oxygenius: Journal Of Chemistry Education, 2023)
This study aims to analyze the chritical thinking skill of university students. The sample of this study was 16 (sixteen) people taken by purposive sampling method. The study was took in Basic Chemistry class and the topic was chemical bonding. The reasearch method was qualitative descriptive reasearch. The instruments developed were test instrument and interview. The test instrument consists of four dimension such as interpretation, analysis, evaluation, and inferension. The result of this study prove that the chritical thinking skill of university students were moderate and the average percentage was 66,0625 The value of each dimensions were 62,75% for interpretation, 55,25% for analysis, 68,75% for evaluation, and the last was 77,5% for inferension.